Red Dragon drill missions to Mars. (December 2017) - Heldmann, Jennifer L.; Stoker, Carol R.; Gonzales, Andrew; McKay, Christopher P.; Davila, Alfonso; Glass, Brian J.; Lemke, Larry L.; Paulsen, Gale; Willson, David; Zacny, Kris
Abstract: We present the concept of using a variant of a Space Exploration Technologies Corporation (SpaceX) Dragon space capsule as a low-cost, large-capacity, near-term, Mars lander (dubbed "Red Dragon") for scientific and human precursor missions. SpaceX initially designed the Dragon capsule for flight near Earth, and Dragon has successfully flown many times to low-Earth orbit (LEO) and successfully returned the Dragon spacecraft to Earth. Here we present capsule hardware modifications that are required to enable flight to Mars and operations on the martian surface. We discuss the use of the Dragon system to support NASA Discovery class missions to Mars and focus in particular on Dragon's applications for drilling missions. We find that a Red Dragon platform is well suited for missions capable of drilling deeper on Mars (at least 2 m) than has been accomplished to date due to its ability to land in a powered controlled mode, accommodate a long drill string, and provide payload space for sample processing and analysis. We show that a Red Dragon drill lander could conduct surface missions at three possible targets including the ice-cemented ground at the Phoenix landing site (68 °N), the subsurface ice discovered near the Viking 2 (49 °N) site by fresh impact craters, and the dark sedimentary subsurface material at the Curiosity site (4.5 °S). Highlights: Mars ice is important for both science and exploration (in situ resource utilization). Studying Mars ice in situ requires a drill to access subsurface samples. A SpaceX Red Dragon lander can accommodate relatively large payloads and deep drills. We present a Red Dragon mission concept to study ice-cemented ground on Mars. The SpaceX Red Dragon capsule capabilities change the paradigm for Mars exploration.